Analysis of Learning Difficulties In Problem Solving Viewed From STIFIn Personality - Rhamadan, Fany Fachri; Kamid, Kamid; Effendi, Muhammad Haris (PRISMA, 2024)
The purpose of this research is to analyze students' learning difficulties in solving mathematical problems on fraction material based on the Sensing, Thinking, Intuiting, Feeling, Instinct (STIFIn) personality type. This type of research is descriptive qualitative at SDN 47 Jambi using a purposive sampling technique with 5 selected students in class IV for the 2022/2023 academic year based on the recommendation of the mathematics teacher who teaches. The data collection techniques used in this research were written tests and interview sheets. The research results show that each subject experiences different learning difficulties when solving problems using Polya steps. In particular, in the step of re-checking answers, all subjects did not know exactly what the appropriate steps were to re-check the correctness of the answers they obtained. Overall, learning difficulties often occur when students want to develop and implement problem solving plans.